Rapid Intravenous Glyceryl Trinitrate in Ischemic Damage (RIGID) After Stroke: Rationale, Design and Protocol for a Prospective Randomized Controlled Trial - Cai, Lipeng; Rajah, Gary; Duan, Honglian; Gao, Jie; Cheng, Zhe; Xin, Ruiqiang; Jiang, Shangqian; Palmer, Peter; Geng, Xiaokun; Ding, Yuchuan (Frontiers in Neurology, 2021)
Background: Despite intravenous thrombolysis and endovascular therapy for acute ischemic stroke (AIS), many survivors still have varying degrees of disability. Glyceryl Trinitrate (GNT), the nitric oxide (NO) donor was reported to induce neuroprotection after AIS. The use of GTN to reduce brain damage after stroke remains yet to be elucidated. This study was designed to explore the safety, feasibility, and preliminary efficacy of intravenous administration of GTN after AIS. Methods: A prospective randomized controlled trial is proposed with AIS patients. Participants will be randomly allocated to GTN group and control group with a 1:1 ratio (n = 30), both groups will be treated with standard therapies according to the current stroke guidelines. Participants allocated to the GTN group will receive intravenous administration of GTN (5 mg GTN in 50 ml saline, with a speed of GTN 0.4 mg/h continued for 12.5 h/day, for 2 days) within 24 hours of symptom onset. Participants allocated to the control group will receive intravenous administration of equal capacity of 0.9% normal saline (NS) (total 50 ml/day, 4 ml/h continued for 12.5 h/day, for 2 days). The primary outcome is safety (neurologic deterioration, death, hypotension, headache), while the secondary outcomes include changes in functional outcome and infarction volume. Discussions: RIGID is a prospective randomized controlled trial and aims to ascertain the safety, feasibility, and preliminary efficacy of intravenous GTN as a neuroprotection strategy after AIS. These results will provide parameters for future studies and provide insights into treatment effects, and possible neuroprotection with reduced brain damage due to GTN in AIS.